Mobility performance measurement in wheelchair basketball - Van der Skikke, R.; Berger, M.; Bregman, D.; Veeger, H. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The current level of play in wheelchair basketball requires a professional approach in optimizing overall game performance, including the mobility performance of each individual athlete. This mobility performance describes the kinematics of the wheelchairathlete combination. The goal of this research was to evaluate a mobility performance measurement method by measuring athletes of different competition level and classification in wheelchair basketball. Given the level of impairment, kinematic based mobility performance was expected to differ between classification groups. Differences due to competition level or gender, were expected to be more subtle and with differences mainly in the strength and skill related (rotational) acceleration. Methods: Using a three inertial measurement unit configuration (Van Der Slikke et al. 2015), wheelchair kinematics of 29 national and international level athletes were measured during a match. The following wheelchair kinematics were measured: displacement, speed, acceleration, rotation, rotational speed and rotational acceleration. The new measurement method was rated as accurate, if expected differences in kinematics showed significant with large Cohen`s d effect sizes. Results: All calculated kinematics differed significantly between classification groups, with less impaired athletes being faster, with higher accelerations. National level players rotated significantly slower than international players and with significantly lower rotational acceleration from standstill. All significant differences uncovered also showed large (> 0.8) Cohen`s d effect sizes. Discussion: The method was concluded to be accurate, since it was able to detect all expected differences in mobility performance between groups. The true value of the new method showed in picking up differences in (rotational) acceleration between competition level or gender groups, something to our knowledge was not measured before. The application of the inertial measurement unit configuration allowed for a more detailed and more accurately quantified measure of wheelchair mobility performance. The method proved to be able to discriminate well between expected differences of aspects of mobility performance, between athletes of different classification, competition level or gender. The measured between-group differences in higher order outcomes, mark the need for including (rotational) acceleration in the quantification of mobility performance. Consequently, the new method measures important aspects of mobility performance and it enables individual athlete evaluation. In such way, it is a crucial tool in professionalizing wheelchair sports, since it supports evaluation of interventions in wheelchair settings or athlete training.